Isocitrate dehydrogenase 1 and 2 mutations, 2‐hydroxyglutarate levels, and response to standard chemotherapy for patients with newly diagnosed acute myeloid leukemia. Issue 4 (13th November 2018) - Brunner, Andrew M.; Neuberg, Donna S.; Wander, Seth A.; Sadrzadeh, Hossein; Ballen, Karen K.; Amrein, Philip C.; Attar, Eyal; Hobbs, Gabriela S.; Chen, Yi‐Bin; Perry, Ashley; Connolly, Christine; Joseph, Christelle; et al.
Abstract : Background: Acute myeloid leukemia (AML) cells harboring mutations in isocitrate dehydrogenase 1 ( IDH1 ) and isocitrate dehydrogenase 2 ( IDH2 ) produce the oncometabolite 2‐hydroxyglutarate (2HG). This study prospectively evaluated the 2HG levels, IDH1/2 mutational status, and outcomes of patients receiving standard chemotherapy for newly diagnosed AML. Methods: Serial samples of serum, urine, and bone marrow aspirates were collected from patients newly diagnosed with AML, and 2HG levels were measured with mass spectrometry. Patients with baseline serum 2HG levels greater than 1000 ng/mL or marrow pellet 2HG levels greater than 1000 ng/2 × 10 6 cells, which suggested the presence of an IDH1/2 mutation, underwent serial testing. IDH1/2 mutations and estimated variant allele frequencies were identified. AML characteristics were compared with the Wilcoxon test and Fisher's exact test. Disease‐free survival and overall survival (OS) were evaluated with log‐rank tests and Cox regression. Results: Two hundred and two patients were treated for AML; 51 harbored IDH1/2 mutations. IDH1/2 ‐mutated patients had significantly higher 2HG levels in serum, urine, bone marrow aspirates, and aspirate cell pellets than wild‐type patients. A serum 2HG level greater than 534.5 ng/mL was 98.8% specific for the presence of an IDH1/2 mutation. Patients with IDH1/2 ‐mutated AML treated with 7+3‐based induction had a 2‐year event‐free survival (EFS) rate of 44% and a 2‐year OS rate of 57%. There was no difference in complete remission rates, EFS, or OS between IDH1/2 ‐mutated and wild‐type patients. Decreased serum 2HG levels on day 14 as a proportion of the baseline were significantly associated with improvements in EFS ( P = .047) and OS ( P = .019) in a multivariate analysis. Conclusions: Among patients with IDH1/2 ‐mutated AML, 2HG levels are highly specific for the mutational status at diagnosis, and they have prognostic relevance in patients receiving standard chemotherapy. Abstract : In this prospective study, isocitrate dehydrogenase mutated patients have higher 2‐hydroxyglutarate levels in serum, urine, and marrow than wild‐type patients, whereas decreased serum 2‐hydroxyglutarate levels on day 14 of treatment, as a proportion of the baseline, are associated with better survival. In isocitrate dehydrogenase mutated acute myeloid leukemia, 2‐hydroxyglutarate levels are highly specific for the mutational status at diagnosis and have a prognostic impact on patients who are receiving conventional treatments.